Methodological Bases of Personnel Policy Formation in the Context of Innovative Development of the Region - Gavrylov, M.; Zerkina, O. (Економічний вісник Донбасу, 2015)
The article discusses methodological basis of personnel policy formation in the context of innovative development of the region. It was found out that establishment and implementation of the state personnel policy,as well as regional and municipal personnel policy, faces a number of difficulties. The components of the concept of regional personnel policy were identified including goals and objectives, mechanisms, principles and strategy. The conceptual basis of mechanism of personnel policy of the region was developed. Conducted studies revealed a number of factors and conditions of external and internal environment, which significantly affects the content and mechanism of implementation of personnel policies. Two groups of regional and sectoral regulations were identified, which must be used in the regional personnel policy for innovative development of the region. The first group helps to determine the perspective of formation and training of innovative personnel and the second group determines the ways of distribution and involvement of personnel.